Las multitudes católicas argentinas en la primera mitad del siglo XX: religión, política y sociedad de masas - Mauro, Diego Alejandro (2015)
The article analyzes the interpretations of the mobilizations and shaping of Catholic crowds in Argentina during the first half of the twentieth century. First, the text identifies the performative effects of the “classical paradigm” of secularization. Secondly, the article proposes relocating the contributions of the political approach, conceived in the context of the 1980s, in a broader explanatory framework, open to recent contributions of social and cultural history. To this end, the paper proposes a model based on the concept of crowd with the aim of discussing different dimensions of the phenomenon, highlighting its multifaceted nature.